Epistolarum iuvenilium libri octo - Decembrii, Petri Candidi (Premio Tesi di Dottorato, 2013)
The three-volume correspondence by Pier Candido Decembrio represents a precious source for the history of northern Humanism and, more generally, for the understanding of the fifteenth-century civilisation. The first epistolary volume covers the time span 1423-1432 and the themes of the epistles cover all the points of the political and literary humanistic debate, from Petrarch to Valla.